Occupational Stigma Perception, Emotional Exhaustion State, and Professional Commitment Response: Understanding the Mechanisms Underlying Hotel Interns’ Perceptions of Career Prospects - Wen, Lei Lei; Xiang, Keheng; Gao, Fan; Zhou, Jieling (Frontiers in Psychology, 2022)
This study uses an integrated model of resource conservation theory and social learning theory to explore the antecedents of hotel interns' perceptions of occupational stigma and to explore the mechanisms inherent to retention willingness. This study first manipulated relevant subjects' experimental materials through a contextual experiment and used a one-way ANOVA to test the effects of competence stereotypes and occupational stereotypes on hotel interns' stigma perceptions, respectively, and then used partial least squares structural equation modeling (PLS-SEM) as a statistical tool and the SmartPLS 3.0 program to validate the model of hotel interns' occupational stigma perceptions-intention. The effects of both competence stereotypes and occupational stereotypes on hotel interns' perceptions of occupational stigma were significant. The results of the partial least squares structural equation model showed that hotel interns' perceptions of occupational stigma significantly contributed to emotional exhaustion and that emotional exhaustion significantly influenced hotel interns’ retention willingness, hotel interns' perceptions of occupational stigma had a significant effect on their retention willingness, while the role of emotional exhaustion as a mediating variable and occupational commitment as a moderator. The inner psychological and behavioral linkage mechanisms of hotel interns’ occupational stigma perceptions and their retention willingness under COVID-19 were explored, and the resource dynamics operating mechanism and professional commitment were also confirmed.